Numerical Analysis of Wake Interaction of Darrieus Tidal Turbine in Shallow Water Application - Marzuki, Najwa Syafiqa; Abdul Rahman, Anas; Abdul-Rahman, Ayu; Rosli, Azzim; Misran, Mohamad Syahfiq; Wan Zulkafli, Wan Muhammad Fadhli Arif; Ramadhan Basiddiq, Ramadhan Ahmed (Journal of Advanced Mechanical Engineering Applications, 2022)
Malaysia is rich in natural resources including coal and fossil fuels. These natural resources, however, will diminish and pollute the ecosystem. Thus, researchers have proposed the use of renewable energy sources such as solar, wind, wave, and other energies as potential solutions to resolve the issue. This study focuses on tidal energy, specifically the vertical axis tidal turbine (VATT) for shallow water application. While majority of the VATT research shows that this device can work effectively in deep water, its effectiveness in shallow water has yet to be explored comprehensively. To analyse the turbine's performance, Computational Fluid Dynamics (CFD) method was applied. The Darriues turbine was used in this study since it is the ideal turbine design for shallow water in Malaysia with an average current speed of 1.0 . The Darrieus turbine model used in this project is 5 metres tall and 4.3 metres in diameter. The simulation was evaluated based on wake characteristics. The Darriues turbine was designed using the NACA0018 airfoil. Following the results of single turbine analysis, the wake has recovered to its ambience velocity at 60 metres behind the device. The wake generation due to multi-row configuration of the devices was also examined. The three-turbine configuration verifies the concept that installing two turbines side by side boosts the performance significantly. Notably, the improvement is sufficient to mitigate the adverse effects due to the turbulence wakes from upstream turbines. The findings demonstrate that by employing a staggered design (1 device upstream and 2 devices downstream), the wake can recover its initial velocity faster due to a shorter wake generation distance.